Robust estimation of vertical wheel forces via modulation-based sensor fusion - Segura Rojas, Juan de Dios (2019)
Since its introduction by Shinbrot, numerous variations of parameter identification based on the Modulating Function Technique (MFT) have been developed. Recently researches have achieved to estimate also states through this method. In this thesis, the MFT is utilized for the estimation, of both parameters and states, that lead to observe the behaviour of the vertical suspension forces on a vehicle over time. In order to deal with the frequency disturbances present by perturbations as measurement noise and vibrations, the Fourier Modulating Function (FMF) as a kernel is proposed. Furthermore, this method is implemented with the concept of sensor fusion. The estimation that results after the implementation of an adaptive observer during the present work is going to show the robustness of the studied technique.